Implementation of the readathon program and library socialization to enhance critical thinking skills, reading comprehension, and literacy of students at SMP Negeri 34 - Yudisman, Septevan Nanda; Jalinur, Jalinur; Iman, Ramdhani Nur (Library of Sultan Agung Islamic University, 2025)
This study aims to evaluate the effectiveness of the Readathon Program and library socialization in enhancing critical thinking skills and reading comprehension among students at SMP Negeri 34 Kota Bekasi. Reading is a fundamental skill essential for learning and developing students' critical thinking abilities. According to Anisa et al. (2021),